The impact of lumbar hyperlordosis on dynamic knee valgus during single-leg jump landing and squat in male college football players - Zandi Shahrzad; Ardakani Mohammad Karimizadeh; Dehcheshmeh Mohammad Sadeghi (Biomedical Human Kinetics)
Study aim: Dynamic knee valgus is one of the most common reasons for knee instability during functional activities in sports. Lumbar hyperlordosis, as an abnormal posture, is associated with decreased knee stability due to altered neuromuscular function of the lower limb muscles. This study aimed to investigate the impact of lumbar hyperlordosis on dynamic knee valgus during single-leg jump landing and squat in male college football players.